Social Prejudice, Ethnicity, and Effectiveness of Communication, Against Tolerance Between Religious People in Sidoarjo Regency - Adimas Mahakim; Totok Wahyu Abadi (Indonesian Journal of Islamic Studies, 2021)
This study aims to describe and explain social prejudice between religious communities in Sidoarjo Regency. This research is based on a bombing case that occurred some time ago which was carried out by several individuals and occurred in the Sidoarjo area which is related to inter-religious communities. This research uses quantitative research. Data was collected by means of interviews, observations, and relevant studies. The data collection technique used is by using a questionnaire or questionnaire method. The results of this study indicate that partially or individually the social prejudice variable has a significant value on religious tolerance in Sidoarjo Regency of 0.843; the ethnicity variable has a significant value on religious tolerance in Sidoarjo Regency of 0.729; and the communication effectiveness variable has a significant value on religious tolerance in Sidoarjo Regency of 0.741 that the independent variables are rejected by the dependent variable. Then if it is reviewed simultaneously or together with the variables of social prejudice, ethnicity and the effectiveness of interpersonal communication on tolerance between religious communities in Sidoarjo Regency it is 3% while the remaining 97% is influenced by other variables outside the variables used in this study.